2022
DOI: 10.1186/s43046-022-00113-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality within the first year post-hepatectomy for hepatocellular carcinoma

Abstract: Background Hepatic resection (HR) for hepatocellular carcinoma (HCC) is safe with good perioperative and long-term oncologic outcomes. There is a paucity of data with regards to intermediate-term outcomes (i.e., beyond 90-day and within 1-year mortality). This paper studies the risk factors for within 1-year mortality after elective HR with curative intent in patients with HCC. Methods An audit of patients who underwent curative HR for HCC from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The potential cause may be that unpublished studies reported negative results. In addition, the prognosis of HCC is not only determined by PLR but also influenced by multiple factors such as surgical complications ( 54 ). It is better to consider all the prognostic factors together in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The potential cause may be that unpublished studies reported negative results. In addition, the prognosis of HCC is not only determined by PLR but also influenced by multiple factors such as surgical complications ( 54 ). It is better to consider all the prognostic factors together in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in patients with large tumors and cirrhosis, more strict selection criteria for hepatectomy are required, especially emphasizing the evaluation of cirrhotic severity. Some studies suggested that the 90-day mortality was usually higher than the 30-day mortality (39,40). The Japanese National Clinical Database showed the 30-and 90-day mortality rates after hepatectomy to be 2% and 4%, respectively (40).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies did not specify which postoperative complications the patients experienced, and only 6 of the 24 studies[ 22 , 27 , 30 , 31 , 34 , 37 ] specified if the patients developed PHLF. Since PHLF has been found to be an independent predictor of mortality[ 2 ], the development of PHLF after HCC resection may be more indicative of the safety profile than complication rates alone. Thus, to improve the safety profile assessment of surgical resection, more precise reporting of major postoperative complications, particularly PHLF, and reporting of the 90-d mortality rate are required.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most prevalent type of primary liver cancer[ 1 ]. It is the third most common cause of cancer-related deaths worldwide and has the fifth-highest incidence rate of cancers[ 2 ]. Currently, most HCCs develop secondary to underlying liver disease, often due to chronic hepatitis B or C virus infection[ 3 ].…”
Section: Introductionmentioning
confidence: 99%